1993
DOI: 10.1177/030751339307900107
|View full text |Cite
|
Sign up to set email alerts
|

Amethyst Mining in the Eastern Desert: a Preliminary Survey at Wadi El-Hudi

Abstract: The most important of the archaeological remains at Wadi el-Hudi are a series of amethyst mines of the pharaonic period. Inscriptions associated with the site were published by Ahmed Fakhry in 1952, but the Middle Kingdom settlement and fortress adjacent to the mines were only briefly described. A preliminary survey of the site, undertaken in November 1992, has provided sufficient new data to allow the archaeological significance of the Wadi el-Hudi mining settlements to begin to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although Rothenberg (1979) and Chartier-Raymond et al (1994) undertook more general surveys of the mines and described other aspects of the archaeological record at Serabit el-Khadim, broadening our understanding of the social context of gemstone mining by reducing the reliance on textual sources still remains. Shaw (1998Shaw ( , 2002 has attempted to move analysis of gemstone mining in Egypt into a more thorough assessment of the social, political and economic backdrop from archaeological research of the production sites, in particular at Wadi el-Hudi (Shaw, 1998;Shaw and Jameson, 1993). Nevertheless, given pharaonic Egypt's extraordinary consumption of raw materials, the potential of production sites to provide insights into the social milieu on both a micro and macro-level still remains undervalued.…”
Section: Abstract Gemstonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Rothenberg (1979) and Chartier-Raymond et al (1994) undertook more general surveys of the mines and described other aspects of the archaeological record at Serabit el-Khadim, broadening our understanding of the social context of gemstone mining by reducing the reliance on textual sources still remains. Shaw (1998Shaw ( , 2002 has attempted to move analysis of gemstone mining in Egypt into a more thorough assessment of the social, political and economic backdrop from archaeological research of the production sites, in particular at Wadi el-Hudi (Shaw, 1998;Shaw and Jameson, 1993). Nevertheless, given pharaonic Egypt's extraordinary consumption of raw materials, the potential of production sites to provide insights into the social milieu on both a micro and macro-level still remains undervalued.…”
Section: Abstract Gemstonesmentioning
confidence: 99%
“…Yet at Stela Ridge, the resource was almost completely worked out, presumably by the late twelfth Dynasty when the ceramic record ends. The resource at Wadi el-Hudi was also worked out, but this could have been due to later exploitation in the Roman Period (Fakhry, 1952;Shaw and Jameson, 1993). Hence, it cannot be concluded that changes in dynastic succession to short reigns in the thirteenth Dynasty would necessarily have contributed to the perceived decrease in mining expeditions, as Quirke (1991: 139) points out.…”
Section: ■ Maintaining the Flow: Macro-level Procurement Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Old Kingdom and early Middle Kingdom, the region to the south of the first Nile cataract at Aswan represented the hostile southern frontier of Egypt proper. Exploitation of the amethyst mines at Wadi el-Hudi, about 35 km southeast of Aswan, appears to have peaked in the Middle Kingdom, a period of many inscriptions and graffiti at the site (Fakhry 1952;Sadek 1980-85;Shaw & Jameson 1993). Three distinct areas of Wadi el-Hudi were in use during the Middle Kingdom: a low hill adjoining an amethyst quarry and surmounted by the remains of a rough stone fortified enclosure, containing about 40 drystone workmen's shelters; another hill, about 200 m southeast of the first, with a large number of Middle Kingdom texts and drawings carved into the rocks at its summit; and a rectangular drystone fortified settlement (70 x 50 m), a further 400 m to the south, associated with two amethyst quarries (see FigURES 5 & 6).…”
Section: Planned and Fortified Settlements: Organizational And Defensmentioning
confidence: 99%
“…Since the 1970s a few projects have begun to explore the full archaeological potential of Egyptian quarries and mines (Dreyer & Jaritz 1983;Shaw 1986; Rothenberg 1988;Caste1 & Soukiassian 1989;Harrell 1989;Arnold 1991;Shaw & Jameson 1993). Others have concentrated on scientific provenancing of the minerals used in monumental structures, statuary and funerary equipment (Klemm & Klemm 1979;1981;Bowman et al 1984;Greene 1989; Middleton & Bradley 1989) or the study of pharaonic stone-working and masonry techniques, often using experimental methods (Stocks 1986;1989;1993;Moores 1991;Isler 1992).…”
Section: Introductionmentioning
confidence: 99%